O tratamento (didático) do género artigo de opinião em diferentes livros didáticos de lingua portuguesa - Oliveira, Adriana Santos de (2016)
This study presents an analysis of the didactic treatment given to the opinion piece genre in different didactic books of the Portuguese Language, destined to Elementary School, years 6 to 9, which were published before and after the National Curricular Parameters (BRASIL, 1998). In a general sense, the authors analysed how the opinion piece is treated in language practices presented in five didactic collections, and how this treatment contributed toward broadening the discursive competence of the student. To achieve this goal, the authors adopted the social-discursive approach to the study of this genre (BAKHTIN, 1997; BRONCKART, 2006, 2012), where a theoretical path is followed that considers a brief history, in Brazil, of the Portuguese Language as a subject (SILVA; CYRANKA, 2009; SOARES, 2002a, 2002b) and the didactic book (BEZERRA, 2005; RANGEL, 2005, 2006). In order to analyse the opinion piece as a study object, through the selected didactic collections, the authors followed the guide lines laid down in the National Curricular Parameters of the Portuguese Language (BRASIL, 1998). In particular where it refers to the organization of the pedagogical practice for the study of language, along with the theoretical- methodological contributions from the Geneva group (DOLZ; NOVERRAZ; SCHNEUWLY, 2004), regarding the sequential procedure concerning didactics and the development of language abilities, for the study of the genre in the classroom. The results from the study reveal, besides other questions, that in general the authors from the collections under analysis, through the didactic transposition of the genre, take on a language practice approach, which is somewhat mischaracterized of certain enunciative or articulative properties. Such results have produced an awakening to the need to provide for the teacher didactic material that favours a more dialogic and reflexive relationship from their standpoint with the didactic book, and thus with the very pedagogical practice. Through these and other questions that were identified in the analysis (positive points along with points of improvement), a didactic proposal was elaborated, directed toward the Portuguese Language teacher, which was applied to Elementary School year 9, for studying the opinion piece genre as a social practice.